A Systematic Review of Extant of Literature in Weight Loss Marketing - Swallehe, Omary; Mwilongo, Kardo (Indonesian Journal of Educational Research and Review, 2024)
Obesity is a concern throughout the world, in today's digital age many items are marketed as weight loss aids via social media platforms. The main purpose is to analyze studying weight loss marketing, what are the current issues investigated and what is going to be the direction of the topic globally. The paper employed a systematic review of literature in which 34 research papers were investigated. These 34 papers were searched from four databases namely; Google Scholar, Microsoft, Base, Global Health and Research gate. The findings reveal that four topics are studies frequently by the researchers from the studies reviewed. These main topics frequently covered are; the weight loss products development initiatives; the tools/technologies employed in the weight loss marketing; the way the weight loss products have been promoted using different tools and mechanism including the social media and digital marketing platforms and the last topic which attracted the attention of many researchers was on the misrepresentation of the material facts regarding the weight loss products. The findings further reveal that little has been studies regarding the effects/impact of sports marketing on organizational performance from the literature we have reviewed.